Research note: Surrounding landscape and local tree structure explain wear in boreal urban forests - Korhonen, Aku; Hamberg, Leena (Elsevier, 2025)
Natural urban green areas in cities are susceptible to degradation due to high levels of recreational use and trampling induced wear. The aim of this study was to relate the amount of wear (paths and worn ground) in boreal urban forests to landscape-scale and local-scale predictors to help assess risks associated with urban densification. Wear was measured in 73 forests in three urban centers in southern Finland and analyzed in relation to surrounding residential density, amount of nearby forest area, and local forest characteristics. Median observed worn cover was 12 % while the most affected sites were over 90 % worn. Higher residential density and smaller forest area had independent exacerbating effects on wear. Wear was also related to tree structure and tended to be larger in forest interiors than near the edge. Our findings showcase how landscape transformations in growing cities may translate into risks of ecological degradation in urban forests.
Keywords: forest recreation; urban green area; urban densification; trampling; walking path; ground vegetation